Heart failure with preserved ejection fraction (HFpEF): Implications for the anesthesiologists - Ajmer Singh; Yatin Mehta (Wolters Kluwer Medknow Publications, 2018)
Heart failure (HF) is a complex clinical syndrome that results from any structural or functional impairment of ventricular filling or ejection of blood. American College of Cardiology Foundation / American Heart Association 2013 guidelines have classified HF into two categories: (i) HF with reduced (≤40%) ejection fraction (HFrEF) or systolic HF, and (ii) HF with preserved (≥50%) ejection fraction (HFpEF) or diastolic HF. Risk factors for HFpEF include age more than 70 years, female gender, hypertension, wide pulse pressure, diabetes mellitus, chronic renal insufficiency, left ventricular hypertrophy, atrial fibrillation, smoking, recent weight gain, and exercise intolerance. Cardiac catheterization and echocardiography are used for the confirmation of diagnosis of HFpEF. Intraoperatively, the hemodynamic goals in patients with HFpEF are avoidance of tachycardia, maintenance of sinus rhythm, and maintenance of higher than usual filling pressure. No specific treatment for HFpEF is established, and therapeutic options include an intravenous diuretic, a beta blocker or calcium channel blocker, a venodilator, and management of co-morbidities.